2015
DOI: 10.1002/joc.4381
|View full text |Cite
|
Sign up to set email alerts
|

Heat waves in Central Europe and their circulation conditions

Abstract: The research objectives were to describe heat waves (HWs) in Central Europe and define the synoptic situations that cause their occurrence. In this article, a hot day was defined as a day when the maximum temperature was above the 95th annual percentile and an HW was considered a sequence of at least five hot days. In the analysed multi-year period and study area, 11 HWs were observed in the north and 51 HWs were observed in the south. The occurrence of HWs was mainly connected with positive anomalies of sea l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

23
107
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 93 publications
(133 citation statements)
references
References 65 publications
(70 reference statements)
23
107
0
Order By: Relevance
“…On average, the lowest number of WSs was recorded between 1981 and 1990, and the highest in the first decade of the twenty-first century. Similar results were also obtained for Central Europe (Tomczyk and Bednorz 2015). The increase in frequency of extreme weather phenomena, including heat waves, was found in the Czech Republic (Kyselý 2010), Poland (Kossowska-Cezak 2010; Tomczyk 2014b), Serbia (Unkašević and Tošić 2009), Ukraine (Shevchenko et al 2014) and Spitsbergen (Tomczyk and Bednorz 2014b).…”
Section: Discussion and Summarysupporting
confidence: 76%
See 1 more Smart Citation
“…On average, the lowest number of WSs was recorded between 1981 and 1990, and the highest in the first decade of the twenty-first century. Similar results were also obtained for Central Europe (Tomczyk and Bednorz 2015). The increase in frequency of extreme weather phenomena, including heat waves, was found in the Czech Republic (Kyselý 2010), Poland (Kossowska-Cezak 2010; Tomczyk 2014b), Serbia (Unkašević and Tošić 2009), Ukraine (Shevchenko et al 2014) and Spitsbergen (Tomczyk and Bednorz 2014b).…”
Section: Discussion and Summarysupporting
confidence: 76%
“…A warm spell (WS) was considered to be a sequence of at least five relatively warm days. The similar method for distinguishing heat waves was applied earlier in the analysis for the occurrence of heat waves in Central Europe (Tomczyk and Bednorz 2015) and for the variable climatic conditions of the Arctic (Tomczyk and Bednorz 2014b).…”
Section: Introductionmentioning
confidence: 99%
“…They have become common during summertime in Bulgaria and south Romania (Simeonov et al, 2013), with dangerous impacts on agriculture associated with increased heat stress episodes. As recently presented at the EU General Assembly 2016, the summer of 2015 was the warmest ever observed in Central Europe, especially due to overall severity of HW (Lhotka et al, 2016), continuing the trend identified by Tomczyk and Bednorz (2016) of significantly increased numbers of HW between 2001 and 2010 as compared to [1981][1982][1983][1984][1985][1986][1987][1988][1989][1990]. Similarly, according to , the CMR has witnessed decreasing trends in cold-related indices, especially in the number of frost days, and increasing trends in warm-related ones.…”
Section: Air Temperaturementioning
confidence: 55%
“…Changes in air temperature in different regions of Europe have shown upward trends, with frequent occurrence of extremely hot months, especially during summertime (Tomczyk and Bednorz, 2016). In Central Europe, the average number of hot days has increased over the past ten years, occurring mostly between April and October and with maxima in June through August (Tomczyk and Bednorz, 2016).…”
Section: Air Temperaturementioning
confidence: 99%
See 1 more Smart Citation